2021
DOI: 10.3389/fmicb.2021.727105
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Changes of Rhodosporidium kratochvilovae at Low Temperature

Abstract: Rhodosporidium kratochvilovae strain YM25235 is a cold-adapted oleaginous yeast strain that can grow at 15°C. It is capable of producing polyunsaturated fatty acids. Here, we used the Nanopore Platform to first assemble the R. kratochvilovae strain YM25235 genome into a 23.71 Mb size containing 46 scaffolds and 8,472 predicted genes. To explore the molecular mechanism behind the low temperature response of R. kratochvilovae strain YM25235, we analyzed the RNA transcriptomic data from low temperature (15°C) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 98 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…We also found that the level of carotenoid and trehalose biosynthesis increased significantly at a low temperature. Therefore, low-temperature adaptation in YM25235 might involve multiple mechanisms [25][26][27]. However, whether an increase in the level of carotenoid biosynthesis at low temperatures is associated with low-temperature adaptation in YM25235 remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that the level of carotenoid and trehalose biosynthesis increased significantly at a low temperature. Therefore, low-temperature adaptation in YM25235 might involve multiple mechanisms [25][26][27]. However, whether an increase in the level of carotenoid biosynthesis at low temperatures is associated with low-temperature adaptation in YM25235 remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence motif 5′-N(20)-NGG-3′ was identified. Since the sgRNA scaffold needs to be complementary to prevent potential off-target sites from being targeted [ 53 ], the selected protospacer was searched using the blastn program in the genome of the R. kratochvilovae strain YM25235 [ 27 ]. Finally, one sequence motif with high CRISPOR scores and no off-target sites was selected for constructing the sgRNA transcription vectors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the more represented pathways MAPK signaling, spliceosome, ribosome, and autophagy were observed, especially in P. glacialis and G. martinii . In a genomic and comparative transcriptomic study of a cold-adapted oleaginous yeast R. kratochvilovae , cultivated at 15°C and 30°C, the significantly downregulated genes were primarily related to metabolic and cellular processes and cellular organelles, whereas the MAPK signaling pathway was among overrepresented pathways ( Guo et al, 2021 ). A recent study of Chen et al (2022) demonstrated that the overexpression and knockout of the MAP-Kinase HOG1 played an important role in cold adaptation of R. kratochvilovae , mainly by promoting the biosynthesis of polyunsaturated fatty acids, such as linoleic acid and linolenic acid, and glycerol ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Rhodosporidium kratochvilovae strain YM25235 subjected to low-temperature stress, 1,300 differentially expressed genes (DEGs) were detected by next-generation deep sequencing technology (RNA-seq). From them, the pathways included the MAPK signaling pathway, metabolic pathways, and amino sugar and nucleotide sugar metabolism were overrepresented ( Guo et al, 2021 ). The MAP-Kinase HOG1 would play a role in cold adaptation in R. kratochvilovae by promoting biosynthesis of polyunsaturated fatty acids and glycerol ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%